(untitled) (Research, Society and Development, 2023)
Aim: to investigate and describe, through a systematic review, the biological behavior and osteogenic potential of composite biomaterials containing hydroxyapatite (HA), alginate and gelatin, in different associations, after in vivo implantation. Materials and Methods: for the search and selection of articles, the Medical Literature Analysis and Retrieval System Online (PubMed/MEDLINE) and Scientific Electronic Library Online (SciELO) databases were used, published between 2012 and 2022, using the descriptors: “bone regeneration”; “biocompatible material”; “durapatite”; “alginate”; “gelatin”. Initially, an association was made with the Boolean operator "OR" between the descriptors and their respective entry terms, considering that the MeSH and DeCS platforms use different terms to refer to the same keywords. Subsequently, the "AND" operator was used in nine associations between the descriptors. Results: during the searches, 1939 articles were located. After using the inclusion and exclusion criteria, 16 studies were included in the review. The main themes found in the searches were: HA and Alginate; HA and Gelatin; HA, Alginate and Zinc; HA, Gelatin and mesenchymal cells; HA, Alginate and Chitosan; HA, Alginate and Silk Fibrin; HA, Gelatin and titanium dioxide; HA, Alginate and Gelatin. It was observed that HA, when associated with alginate or gelatin, has improved its osteogenic properties. Final Considerations: HA composites associated with alginate and gelatin provide a range of applications and promising strategies applied to bone repair. Studies have shown that these composites have great potential for application in Bone Tissue Bioengineering.